Symposium 12:Usefulness of continuous monitoring and infusers in type 2 diabetes mellitus - María Lidia Ruiz Morosini (Revista de la Sociedad Argentina de Diabetes, 2022)
In recent years, the advent of new technologies such as continuous glucose monitoring (mcg) have had an impact on glycemic control and quality of life, providing a comprehensive view that provides much more data such as trends, glycemic variability, inadvertent hypoglycemia and patterns during sleep, prolonged fasting, physical activity and intercurrences. Even so, in people with type 2 diabetes, the evidence to recommend RT-CGM or Flash/IS-CGM was scarce, studies have been published, such as Mobile, Diamond and Optimize, exposing the benefit with achievement of lower HbA1c and hypoglycemia and longer Time in range. The strong evidence of association between TIR and coefficient of variation with cardiovascular disease and plaque vulnerability raises the importance of optimizing control in this population.